1995
DOI: 10.1128/aem.61.6.2099-2107.1995
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic diversity of chlorine-resistant Methylobacterium strains isolated from various environments

Abstract: Strains of pink-pigmented facultative methylotrophs which were isolated previously from various environments and assigned tentatively to the genus Methylobacterium were characterized in comparison with authentic strains of previously known species of this genus. Most of the isolates derived from chlorinated water supplies exhibited resistance to chlorine, whereas 29 to 40% of the isolates from air, natural aquatic environments, and clinical materials were chlorine resistant. None of the tested authentic strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…In the phylogenetic analysis, since the strains belonging to Group B formed 74.1%, it became clear that there are many strains belonging to Group B in tap water, and it was in agreement with results reported by Hiraishi et al (11). These isolates were investigated with regard to the relationship with the isolated areas and the residual chlorine concentration in tap water, but no marked tendencies were noted in geographical differences or with regard to chlorine resistance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the phylogenetic analysis, since the strains belonging to Group B formed 74.1%, it became clear that there are many strains belonging to Group B in tap water, and it was in agreement with results reported by Hiraishi et al (11). These isolates were investigated with regard to the relationship with the isolated areas and the residual chlorine concentration in tap water, but no marked tendencies were noted in geographical differences or with regard to chlorine resistance.…”
Section: Discussionsupporting
confidence: 87%
“…The objective of this study was to elucidate which species of Methylobacterium inhabit tap water in hospitals. Since Methylobacterium species were isolated from various samples, including aqueous environments (11,15), it was showed that the bacteria were widely distributed in natural environments. Because of the diversity in the properties among the strains, new species have been reported continually since 2000 (1,8,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylobacterium is frequently found in oligotrophic environments, such as water reservoirs and drinking water vessels as well as clean habitats (La Duc et al, 2007). Their resistance to high levels of chlorine has been described (Hiraishi et al, 1995), and it is possible that cleaning agents used in these assembly Table 4. Sequences of bacterial species retrieved from the surrounding air of various spacecraft assembly facilities…”
Section: Discussionmentioning
confidence: 99%
“…For example, the finished water sample collected on 8 September 2017 contained a high relative abundance of Stramenopiles (67% of the total operational taxonomic units (OTUs), table S12), which is commonly associated with algae [31]. A surge in Methylobacterium was also noted in samples taken from City B's distribution system on the first two sampling dates (table S12); this phylum is often associated with soil enviornments [32]. This surge in plant-and soil-associated bacteria coincides with a surge in TOC in City B's raw and finished waters.…”
Section: City Bmentioning
confidence: 99%